The Theory and Practice of Sensory Evaluation of Vinegar: A Case of Italian Traditional Balsamic Vinegar - Fusheng Chen; Yanqin Ma; Giuseppe Corradini; Paolo Giudici (Foods, 2025)
Sensory analysis is a very powerful and useful tool that is used for a variety of foods. But for vinegar, the relevant sensory evaluation system is not satisfactory since there are still some issues, such as the tendency for score conservatism, descriptor redundancy, sensory fatigue and other cognitive issues. In this review, the theory of the sensory evaluation of vinegar is first introduced, and then the application of sensory evaluation is summarized for vinegar, especially for Italian Traditional Balsamic Vinegar. By improving the scoring system and enhancing the tasting conditions, the reliability of vinegar sensory evaluation can be further increased and provide a solid support for vinegar quality control and market promotion.